Description of Characteristics and Behavior Prevention of UTIs in Mothers of Children Aged 1-3 Years - Lili Suryani; Meri Neherta; Rahmadevita (GoAcademica Research & Publishing, 2023)
Urinary tract infections in children in Indonesia reach 90-100 cases per 100,000 population per year or about 180,000 new cases per year. Risk factors for urinary tract infections in children include environmental sanitation, personal genital hygiene, child nutritional status, age, and gender. This study aims to look at the characteristics of health education respondents to prevent urinary tract infections in children aged 1-3 years. This study uses a descriptive design with a quantitative approach. This research was conducted from May to August 2023. The population in this study were mothers who had children aged 1-3 years in the Pondok Tinggi Health Center Region. The sampling method is non-probability sampling, namely by means of Purposive Sampling, a sample of 110 people was obtained. The research results showed that respondents: 85.5% were early adults (20-35 years), 82.7% were housewives, 62.7% had high school education, 56.4%) were of the Kerinci ethnicity. Then 72.7% had children aged 2-3 years, 63.6% of the respondents' children were female, 73.6% of the children had normal weight, and 89.1% of the children had normal height. Then 44.5% of respondents had poor knowledge of environmental sanitation, 51.8% had poor knowledge of genital hygiene, 45.5% had poor knowledge of nutritional value. Furthermore, 60.0% have negative attitudes about environmental sanitation. 63.6% of respondents had a negative attitude towards genital hygiene, as many as 60.0% had a negative attitude towards the importance of nutritional value, 59.1%% had poor environmental sanitation practices, as many as 53.6% had poor genital hygiene practices and 43.6% had poor nutritional value measures. Where it can be concluded that research respondents have insufficient knowledge, negative attitudes and poor actions to prevent urinary tract infections. It is hoped that the responsible officers (Health Service) can provide interventions to increase knowledge, attitudes and actions to prevent urinary tract infections in mothers who have children aged 1-3 years.